2021
DOI: 10.1101/2021.03.31.437925
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 immune evasion by variant B.1.427/B.1.429

Abstract: SARS-CoV-2 entry is mediated by the spike (S) glycoprotein which contains the receptor-binding domain (RBD) and the N-terminal domain (NTD) as the two main targets of neutralizing antibodies (Abs). A novel variant of concern (VOC) named CAL.20C (B.1.427/B.1.429) was originally detected in California and is currently spreading throughout the US and 29 additional countries. It is unclear whether antibody responses to SARS-CoV-2 infection or to the prototypic Wuhan-1 isolate-based vaccines will be impacted by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
186
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(199 citation statements)
references
References 73 publications
11
186
2
Order By: Relevance
“…However, we observed a reduction in some sera to mutation N439K (0.530.45) as reported in (40), which was not observed when Δ69-70 was added (Fig. 2H), and also, as reported in (59), in mutation L452R (0.480.23) that is associated with the most recent variants of concern B.1.427/9. Importantly, we tested BNT162b2-elicited plasma (collected after the first and second dosage of the Pfizer-BioNTech vaccine) for their capacity to neutralize the spike-pseudotyped particles, expressing WT spike protein or mutants bearing all defining mutations of the variants of concern B.1.1.7, B.1.351 and P.1.…”
Section: Neutralization Assays On Spike-pseudotyped Viruses To Evaluate Synergetic Effects Of Mutationssupporting
confidence: 84%
“…However, we observed a reduction in some sera to mutation N439K (0.530.45) as reported in (40), which was not observed when Δ69-70 was added (Fig. 2H), and also, as reported in (59), in mutation L452R (0.480.23) that is associated with the most recent variants of concern B.1.427/9. Importantly, we tested BNT162b2-elicited plasma (collected after the first and second dosage of the Pfizer-BioNTech vaccine) for their capacity to neutralize the spike-pseudotyped particles, expressing WT spike protein or mutants bearing all defining mutations of the variants of concern B.1.1.7, B.1.351 and P.1.…”
Section: Neutralization Assays On Spike-pseudotyped Viruses To Evaluate Synergetic Effects Of Mutationssupporting
confidence: 84%
“…Pseudoviruses of multiple variants and single mutants at RBD sites presumably related to these variants were examined for their ability to infect four SARS-CoV-2 susceptible cells. No signi cant enhancements of infectivity were observed among the tested variants, compared with the D614G reference strain, while the L452R mutation and B.1.429 variant exhibited slightly increased infectivity; these ndings were consistent with the reports by MaCallum et al 16 . In addition, we also found slight enhancements of infectivity involving the B.1.525, B.1.526-2, and B.1.1.318 variants, suggesting that these variants should receive close attention.…”
Section: Discussionsupporting
confidence: 92%
“…A recent report revealed that the L452R mutation reduced or abolished neutralizing activity of 14 out of 35 RBD-specific mAbs including three clinical stage mAbs. 21 Another recent study 22 has demonstrated that the mutation L452R can escape from human leukocyte antigen (HLA)-24-restricted cellular immunity and can also increase viral infectivity, potentially promoting viral replication. Hence the double mutant combination noted in this study that may result in neutralization escape of specific mAbs needs to be further experimentally validated.…”
Section: Discussionmentioning
confidence: 99%